Eurasian Cooperation in Science and Higher Education: Prospects of Neofunctional «Spillovers» - V. M. Fatykhova (Vestnik MGIMO-Universiteta, 2019)
Development of the global knowledge-driven economy requires the intensification of scientific, technical and educational cooperation in order to ensure competitiveness, technology transfer and improve the quality of life of the people. This task is particularly relevant in integration associations: over the past 20 years the European Union has proved the effectiveness of scientific, industrial and educational cooperation in the interests of economic integration. The Eurasian economic Union is only at the beginning of this promising path and faces a number of difficulties.The purpose of the article is to analyze the state and prospects of cooperation of the EAEU member States in the field of science and higher education. The main thesis of the author is that the launch of the process of the common Eurasian educational space will increase the effectiveness of achieving the goals of the Union Treaty, improving the quality and quantity of economic growth. The pilot projects of the Eurasian technology platforms, especially in the space field, not only serve as examples of successful interaction of mixed research teams, but also give a political signal of the readiness of countries to coordinate their national interests with long-term integration plans. Cooperation in the field of higher education lays the Foundation for a single market of qualified labor resources, contributes to the formation of the personnel potential of the Association, the development of relations between the youth of the "Eurasian five", the interpenetration of common values and ideas.Political and financial support for Russia gives an important impetus to the development of scientific and educational cooperation in the EAEU. However, many projects are hold up due to the lack of popularization of the ideology of Eurasianism and nationalist rhetoric rooted in the partner countries of Russia. The solution of these problems is in the adoption of joint measures to strengthen ties in the triangle «comprehensive information support of the Eurasian idea – scientific and educational cooperation – loyalty of the people to the integration project». If we extrapolate the neo-functional principle of «spillover» to the scientific and educational component of the integration processes, then with the effective implementation of such measures, if successful, this strategy will lead to the formation of a public demand for deepening integration cooperation, including the field of science and education, which, in turn, will bring benefits of economic integration and strengthen the international competitiveness of the EAEU.